Hydrothermal treatment followed by enzymatic hydrolysis and hydrothermal carbonization as means to valorise agro- and forest-based biomass residues. (July 2017) - Wikberg, Hanne; Grönqvist, Stina; Niemi, Piritta; Mikkelson, Atte; Siika-aho, Matti; Kanerva, Heimo; Käsper, Andres; Tamminen, Tarja
Graphical abstract: Highlights: Biomass composition defines its feasibility for alternative process routes. High carbohydrate content was favourable for the saccharification route. Hydrothermal carbonisation yields were high for biomasses with high lignin contents. Methodology developed for lignin quantitation in the presence of protein and ash. Abstract: The suitability of several abundant but underutilized agro and forest based biomass residues for hydrothermal treatment followed by enzymatic hydrolysis as well as for hydrothermal carbonization was studied. The selected approaches represent simple biotechnical and thermochemical treatment routes suitable for wet biomass. Based on the results, the hydrothermal pre-treatment followed by enzymatic hydrolysis seemed to be most suitable for processing of carbohydrate rich corn leaves, corn stover, wheat straw and willow. High content of thermally stable components (i.e. lignin) and low content of ash in the biomass were advantageous for hydrothermal carbonization of grape pomace, coffee cake, Scots pine bark and willow.